The impact of COVID-19 epidemic on development of micro, small and medium enterprises policy in East Kalimantan government - Fourqoniah, Finnah; Aransyah, Muhammad Fikry (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
This article discusses the efforts of the East Kalimantan Government handling cases of development of micro, small, and medium enterprises (MSMEs) during the COVID-19. The handling strategy can be assessed by understanding the measures, steps, and policies formulated and implemented by the East Kalimantan government. A deliberative policy analysis approach was used to analyze this case. This approach analyzes the narratives and arguments of the authorities to understand decision-making and policy implementation. The writing of this article uses a qualitative approach by utilizing the descriptive analysis method. The data collection technique used is a literature study using books, journal articles, newspapers, online news, and traditional institutions' websites. First, this paper's essential findings are reallocation and refocusing of the Covid-19 Budget for the cost of economic stimulus to strengthen capital for affected businesses and small industry players. Second, relaxation and credit restructuring. Third, the temporary closure policy for cafes or restaurants is due to residents' ignorance or non-compliance with government calls regarding health protocols. As a result, efforts to deal with it have stalled because the wider community does not support it. Combining these three factors complicates the provincial government's efforts to deal with MSMEs' development during the COVID-19 pandemic in East Kalimantan. Policy recommendations for the recovery of MSMEs in East Kalimantan Province, namely increasing the role of Indagkop through fostering and educating MSMEs in utilizing technology to sell online and the one-door policy for MSMEs.